Effect of periodic water-sediment laden flow on damage for steel piles - Liu, Mingwei; Zeng, Liqin; Wu, Linjian; Zhu, Chenhao; Abi, Erdi (Frontiers in Environmental Science, 2022)
Due to the problems of shallow overburden and deep water construction, etc., steel tube piles are mostly used in the substructures of frame-wharves in inland rivers of China, especially in the upper stream of Yangtze River. Affected by the fluctuating backwater area of the Three Gorges, anticorrosion coatings of steel structures generally fell off. The steel piles exposed to the water level fluctuation area are subjected to periodic erosion damage process of water-sediment laden flow, which accelerate the corrosions of the steel pile and greatly affect the durability of the wharf structures. In order to explore the effect of periodic water-sediment laden flow on the damage for steel piles in water level fluctuation area of inland rivers, a series of accelerated periodic erosion tests were carried out in laboratory to acquire the damage laws of steel samples under different working conditions. Results showed that the residual masses of steel samples fluctuated with the increasing number of cycles and that the corrosion depths of steel samples were logarithmically correlated with the experimental time. According to the results of periodic accelerated erosion test based on the water-sediment laden flow and existing corrosion theory, a time-dependent model for the corrosion of steel components under water-sediment laden flow was established, as well as a evaluated method for the resistance degradation of steel pile was proposed. Finally, after 20 years, the actual resistance of the steel structure exposed to the water level fluctuation area was less than 60% compared by the initial structural resistance. The research results can provide important guiding significance for reasonably predicting the durability of hydraulic steel structures.